Conflict and Cyber-espionage: Ridding the World of Cyber War? - Ford, Shannon (2014)
This paper examines the argument that espionage is a distinct framework for evaluating conflict in cyberspace and that it should displace discussions of cyber war in most cases. I start by outlining Thomas Rid’s recent argument that most discussions of “cyberwar” are exaggerated because there is no known act of “cyber” war, when war is properly defined. An important part of his argument is that the most widespread use of state-sponsored cyber capabilities is for the purpose of espionage, which, he argues is neither crime nor war. I agree with Rid that the novelty of cyber conflict makes it unclear what actions constitute an act of war and that there is an important distinction between acts of war and espionage. But then I examine his assertion that physical violence is a necessary condition of war and that attacks from cyberweapons cannot meet this condition because they are not physically violent and, in many cases, will not even result in permanent damage. I argue that Rid has misappropriated Clausewitz’s concept of war and there remain no shortage of serious concerns when it comes to the use of cyberweapons. First, the damage to software caused by conflict in cyberspace has the potential to harm critical infrastructure and threaten the lives of people. Second, there is the potentital that the use of cyberweapons could lower the threshold for conflict between states. Third, cyberweapons might also increase the likelihood of civilians being targeted and/or becoming victims of disproportionate attacks on joint-use infrastructure.